Peran Audit atas Persediaan dalam Meningkatkan Efektivitas Pengendalian Internal Perusahaan Dagang - Fatmawati, Fatmawati; Nurtang, Nurtang; Chaeril Akbar; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to analyze the strategic role of inventory auditing in enhancing the effectiveness of internal control within trading companies by examining how structured audit procedures, risk-based assessments, and the integration of digital tools contribute to strengthening financial reporting reliability and operational efficiency. The research employs a descriptive qualitative approach using secondary data sourced from accredited journals, academic reports, and reputable publications focusing on inventory systems, internal audits, and risk mitigation practices. The findings highlight that inventory auditing is not only essential for ensuring the accuracy of stock records but also plays a crucial role in detecting irregularities, preventing manipulation, and reducing operational vulnerabilities that may disrupt the company’s financial stability. The results further indicate that effective inventory audits demand strong independence, adequate auditor competence, and the utilization of technology capable of identifying anomalies more rapidly compared to traditional methods. Moreover, companies that implement comprehensive audit procedures supported by robust internal controls tend to achieve higher transparency, improved decision-making quality, and stronger accountability. Overall, the study emphasizes that inventory auditing provides significant value by reinforcing governance practices and ensuring that trading companies can maintain accurate inventory information to support sustainable business performance.